2012
DOI: 10.1097/ta.0b013e31825ac49e
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blinded, placebo-controlled pilot trial of anticoagulation in low-risk traumatic brain injury

Abstract: Therapeutic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 19 publications
0
86
1
2
Order By: Relevance
“…8,46 Phelan et al conducted a pilot randomized trial with an analysis of non-inferiority to examine the effects of prophylactic enoxaparin on progression of ICH among low-risk TBI patients. More specifically, TBI patients presenting within 6 hours of injury with small injury patterns and stabilized CT scans at 24 hours were considered having low risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,46 Phelan et al conducted a pilot randomized trial with an analysis of non-inferiority to examine the effects of prophylactic enoxaparin on progression of ICH among low-risk TBI patients. More specifically, TBI patients presenting within 6 hours of injury with small injury patterns and stabilized CT scans at 24 hours were considered having low risk.…”
Section: Resultsmentioning
confidence: 99%
“…Phelan et al and Scudday et al showed that PTP did not increase the incidence of ICH progression among patients with stable hemorrhage patterns. 12,46 The study by Levy et al stressed the importance of ensuring stability of hemorrhage patterns before initiating PTP. 8 The study demonstrated that PTP was safe among patients with a stable CT at 24 hours of admission but it would expose patients with initial ICH progression to a 13-fold higher risk of worsening ICH.…”
Section: Discussionmentioning
confidence: 99%
“…20 In DEEP I, subjects in the low-risk arm with stable injury patterns on repeat scan at 24 h after injury were randomized to receive enoxaparin 30 mg subcutaneously or placebo in a double-blind fashion from 24 to 96 h after injury. After enrolling 62 subjects, no clinical progressions of hemorrhage were noted in either group.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized, double-blinded, placebocontrolled pilot trial of anticoagulation in low-risk traumatic brain injury: The Delayed Versus Early Enoxaparin Prophylaxis I (DEEP I) study 6 Rationale Rationale Rationale Rationale Rationale The timing to initiate VTE chemoprophylaxis in TBI is controversial, given the risk of progression of ICH. Different institutions use different algorithms that are supported by weak evidence and often consider TBI as a binary clinical state -either with or without ICH.…”
Section: Study 3 Study 3 Study 3 Study 3 Studymentioning
confidence: 99%